Two-input boost converter for street-lighting applications. (June 2021) - Abbasi Soltani, Behnam; Sabahi, Mehran; Babaei, Ebrahim; Pouladi, Jaber
Graphical abstract: Image, graphical abstract Abstract: In this paper, a combination of a two-input boost converter and an impedance network is presented for street-lighting applications. In places far from the national grid, due to the reduction of additional power transmission, PV-based LED drivers are a cost-effective method. Switched-inductor impedance-network not only increases the voltage gain, but also reduces the voltage ripple at the output side. One inductor is shared between two input sources, so the volume is reduced. Besides, in order to decrease the overall cost of the system, the voltage stress on the power switches is decreased by using the cascading mode of the power switches. As a result, the proposed converter can be a good candidate for street lighting. All operating modes are analyzed in detail in two separate sections. Finally, a laboratory 60 W prototype is built and tested to verify the accuracy of the theoretical analysis showing an efficiency of 92.8%.